Facile and tailored synthesis of ultrahigh-surface-area clews of carbon nanobelts for high-rate lithium–sulfur batteries. Issue 44 (1st November 2017) - Zeng, Shao-Zhong; Zeng, Xierong; Tu, Wenxuan; Yao, Yuechao; Yu, Liang; Wu, Hongliang; Jin, Wenwu; Huang, Haitao; Zou, Jizhao
Abstract : Hierarchical clews of carbon nanobelts (CsCNBs) with surface area up to 3445 m 2 g −1 have been synthesized by a template-free method from low cost raw materials. Abstract : Hierarchical clews of carbon nanobelts (CsCNBs) with surface area up to 3445 m 2 g −1 have been synthesized by a template-free method from low cost raw materials. The composite of CsCNBs/sulfur displays high initial capacities of 1476, 1021 and 838 mA h g −1 at 1, 3 and 5C, respectively, and ultraslow capacity decay rate of 0.052% per cycle during 300 cycles.